Value-Based Strategic Language Management in Islamic Boarding Schools: Negotiating Communicative Competence and Religious Identity in English Language Programs - Moh. Hafidurrahman; Miftahul Muttaqiin; Ali Ridho; Ahmad Andry Budianto; Fajriyah Fajriyah; Iwan Kurniawan (Gemilang Maju Publikasi Ilmiah (GMPI), 2026)
Despite growing interest in English-language education in faith-based institutions, limited attention has been given to how language policy and strategic leadership shape communicative competence in religious educational settings. This study investigates the strategic management of English language programs in an Islamic boarding school (pesantren) in Indonesia, focusing on the integration of language policy, institutional leadership, and Islamic values in developing students’ communicative competence. Employing a qualitative single-case study design, data were collected through semi-structured interviews, non-participant observations, and document analysis involving 15 participants, including institutional leaders, teachers, language coordinators, and students. The findings reveal that English language programs are strategically managed through value-based language policy, leadership alignment, environmental language regulation, and Islamic moral education. English is positioned not merely as an instructional subject but as an identity-compatible communicative practice embedded within the institution’s religious mission and daily social life. Institutional leaders play a central role in sustaining communicative practices through policy reinforcement, symbolic participation, and structured language environments extending beyond classroom instruction. The study contributes to language policy and communicative competence scholarship through the concept of value-based strategic language management, demonstrating that communicative competence in faith-based educational settings is socially and ideologically mediated rather than culturally neutral. The findings also provide insights for educational leaders seeking to balance global communicative demands with institutional religious identity.